The God who comes : Dionysian mysteries revisited - Taylor-Perry, Rosemarie (Algora Pub., 2003)
The most widely acclaimed and influential religious cult in the ancient Greek world, for almost 2000 years, was the Eleusinian Mysteries, the Mystery Rites of Dionysos and associated Hellenic deities. Drawing participants from Rome, Egypt and all around the Mediterranean, the Mysteries influenced and inspired many of the greatest minds including Aristotle, Homer and Plutarch. But initiates were sworn to secrecy; and with the advent of Christianity, the Roman Empire stamped out this "cult." How did adherents of Hellene Mystery Deities performed their worship? What was the symbolism of the sacred objects and the actions performed? The God Who Comes is a meticulously researched exploration of how and why these rites were performed, based upon archaeological, scholarly and iconographic evidence -- a refutation of facile New Age inventions. Cicero said, "Athens never created anything nobler than those sublime Mysteries through which we became gentler and have advanced from a barbarous and rustic life to a more civilized one, so that we not only live more joyfully but also die with a better hope." The author traces how the rituals were related chronologically; why it seems that many aspects of ritual action are unclear or appear transposed; and why no scholar intent upon probing the hows and wherefores of ancient Mystery rites had ever presented them in any sort of chronological, easily-understood manner. She examines parallels in diverse civilizations including the use of hallucinogens in religious rites, and archetypal deities such as shape-changers (like the Navajo Coyote). The book includes an index, Greek-to-English glossary, extensive footnotes and bibliography